Credit Constraints and Fraud Victimization : Evidence from a Representative Chinese Household Survey - Gao, Nan (World Bank, Washington, DC, 2020)
Using a novel, nationally representative data set on fraud victimization, this paper examines the impact of credit constraints on fraud victimization and potential underlying mechanisms in Chinese urban areas. After controlling for other household characteristics and regional fixed effects, households facing credit constraints are associated with 2.3 percentage points higher probability of becoming fraud victims, and have 20.4 percent higher subsequent economic losses from fraud when they are approached. The results are robust when dealing with the endogeneity of facing credit constraints and when addressing potential sample selection bias. Further analyses show that the personal discount rate (impatience) and the need for social network expansion are critical pathways via which credit constraints affect fraud victimization. The findings suggest that improving financial development is an effective way to reduce fraud victimization.